Maps of rice area in Senegal River Valley based on MODIS time-series and the PhenoRice algorithm - CGIAR Research Program on Rice (2019)
PhenoRice algorithm was piloted and we found that it can provide insights about recent variations in rice cultivation practices in Senegal River Valley. Next step is to use radar data for further improving accuracy of estimation of rice area.